Causal relationships between the parameters of gas discharge visualization and phagocytosis - Valeriy Babelyuk; Anatoliy Gozhenko; Galyna Dubkova; Nazariy Babelyuk; Walery Zukow; Bohdan Kindzer; Marta Kovbasnyuk; Igor Popovych (Kazimierz Wielki University, 2021)
Background. Previously we have been shown that between parameters of GDV and principal neuroendocrine factors of adaptation exist strong canonical correlation. In the next study, we detected very strong (R=0,994) integral canonical correlation between the parameters of GDV and Immunity. This study, conducted in the same contingent, will analyze the relationships between GDV parameters, on the one hand, and Phagocytosis parameters, on the other. Material and Methods. We observed twice ten women and ten men aged 33-76 years without clinical diagnose. In the morning in basal conditions at first registered kirlianogram by the method of GDV by the device "GDV Chamber" ("Biotechprogress", SPb, RF). Than we estimated the parameters of Phagocytic function of neutrophils. Results processed by method of canonical analysis, using the software package "Statistica 5.5". Results. According to the value of the canonical correlation coefficient R with GDV parameters, the registered Phagocytosis parameters are arranged in the following order: activity (0,616), bactericidal capacity (0,493), completeness (0,489) and intensity (0,484) of Phagocytosis of E. coli; completeness (0,482), bactericidal capacity (0,448), activity (0,364) and intensity (0,338) of Phagocytosis of Staph. aureus. Coefficient of canonical correlation between parameters of GDV, on the one hand, and Phagocytosis, on the other hand, makes 0,847. Conclusion. The above data, taken together with the previous ones, state that between parameters of Neuroendocrine-Immune complex and GDV exist strong canonical correlation suggesting suitability of the latter method.